State crises, globalisation, and national movements in north-east Africa - Jalata, Asafa, 1954- (London ; New York : Routledge, 2004)
This book demonstrates that the crises of the Horn states stem from their political behaviour and structural forces.
Book Cover; Title; Contents; List of contributors; Foreword; Preface; The process of state formation in the Horn of Africa in comparative perspective; The racialised and Islamicised Sudanese State and the question of Southern Sudan; Global capitalism and the Oromo liberation struggle: theoretical notes on US policy towards the Ethiopian empire; Two national liberation movements compared: Oromia and Southern Sudan; The Oromo Gada system of government: an indigenous African democracy; Contending democracies: US-sponsored 'democracy' encounters indigenous Oromo democratic forms.
Title from PDF title page (viewed 23 Nov., 2009).
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: State, The; Nationalism -- Africa, Northeast; Globalization -- Political aspects -- Africa, Northeast; Africa, Northeast -- Politics and government -- 1974-; Africa, Northeast -- Ethnic relations; État.; Nationalisme -- Afrique du Nord-Est.; Mondialisation -- Aspect politique -- Afrique du Nord-Est.; Afrique du Nord-Est -- Politique et gouvernement -- 1974-; Afrique du Nord-Est -- Relations interethniques; POLITICAL SCIENCE -- Political Process -- General; Ethnic relations; Globalization -- Political aspects; Nationalism; Politics and government; State, The; Northeast Africa; Since 1974